Risk retention in the European securitization market: Skimmed by the skin-in-the-game methods? - Vivian van Breemen; Claudia Schwarz; Dennis Vink (European Central Bank (ECB), 2023)
We empirically investigated the impact of regulatory risk retention methods on credit ratings and pricing at issuance using a sample of European securitization tranches issued in the period 2011-2021. European regulation is based on the assumption that all risk retention methods homogenously align incentives and interests between originators and investors. We investigated the impact of these methods on the pricing of securitization tranches and found that investors adjust the risk premium at issuance for tranches based on different risk retention methods. We also found that credit ratings (discrepancy) differed depending on the risk retention method used. Finally, we gained a deeper insight into the risk retention methods chosen over time and concluded that originators take deal complexity and capital relief characteristics into consideration when selecting a specific method.
Keywords: G12; G21; G24; G28; 330; risk retention rule; primary issuance spread; credit ratings